Campur Kode pada Unggahan Akun Instagram @ganjar_pranowo : Kajian Sosiolingusitik - M. Furqon Al Maarif; Kundharu Saddhon (Lembaga Pengembangan Kinerja Dosen, 2023)
This research focuses on code mixing that occurs in uploads to the Instagram account @ganjar_pranowo. Data were obtained from Instagram social media relating to multilingual and bilingual interaction processes that occur in society. All data was obtained and presented using a descriptive qualitative approach. The research method used is descriptive qualitative, with data collection techniques using listening techniques. The method used to write data is the equivalent method with the translational equivalent technique. The data consists of uploading sentences in Indonesian, Javanese and English on the Instagram account of Ganjar Pranowo (@ganjar_pranowo). There are 11 data showing internal code mixing, consisting of 6 forms of words, 4 forms of phrases and 1 form of sentences. In internal code mixing, all data is in Javanese. There are 15 data showing external code mixing which are divided into 8 data in the form of words and 7 data in the form of phrases. External code mixing consisted of 14 data in English and only 1 data in another foreign language, namely Korean. The entire function of code mixing on the Instagram account @ganjar_pranowo is to familiarize and attract readers' attention.